PERILAKU FLEXING CULTURE PADA KAUM MILLENIAL (Studi Kasus Masyarakat Pengguna Media Instagram Di Kecamatan Kikim Timur Kabupaten Lahat) - Nova April Liza; Sepriadi Saputra; Gita Astrid (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2025)
This study aims to describe the flexing culture behavior among millennials and identify the factors that influence it, with a focus on Instagram users in Kikim Timur District, Lahat Regency. The background of this study is based on the phenomenon of increasing flexing practices carried out by 210 millennials from 32 villages in Kikim Timur District, with the highest concentration in Linggar Jaya, Purwa Raja, and Lubuk Kuta Villages. This phenomenon raises concerns about shifting social values, social decline, and potential security risks due to flaunting wealth on social media. This study uses a qualitative approach with a case study method, referring to the Value-Expectancy Theory proposed by Martin Fishbein. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that flexing behavior is carried out through various forms of posts, such as showing off hobbies, achievements, collaboration promotions, sales testimonials, and proof of payment. These posts not only aim to build self-image but also open up economic opportunities. Factors driving flexing behavior include the need for social recognition, validation through likes and followers, constructing a more attractive image, and economic motivations such as building a personal brand and expanding business networks. This study illustrates that flexing culture among millennials in East Kikim is the result of the interaction between social and economic needs, and personal communication strategies on social media.